Utilising acupuncture for mental health; a mixed‐methods approach to understanding the awareness and experience of general practitioners and acupuncturists. (May 2020) - Roberts, Kate; Dowell, Anthony; Nie, Jing-Bao
Abstract: Background: Mental health presents a significant burden of disease and a large, and increasing, number of patients are self-selecting forms of CAM, including acupuncture, as an adjunct, or standalone treatment for the management of their mental health. General practitioners (GPs) play an important role in integrated care management of primary mental health, and in most cases act as the primary provider and access point for further services. However, the interaction and collaboration between GPs and acupuncturists in relation to shared mental health care has not been investigated. This research explores interprofessional communication between GPs and acupuncturists in New Zealand concerning mental health care. The aim of this research was to understand the barriers to communication, and to facilitate collaboration between the two participant groups. Methods: The project utilised a mixed methods multiphase design, with both qualitative and quantitative inquiry, and involving the convergence of data and analyses. A nationwide survey of 400 GPs and 250 acupuncturists was conducted. Univariate data was analysed using descriptive statistics, which included frequencies and percentages for categorical data. This was followed by individual semi-structured interviews of 13 purposively sampled acupuncturists, and 14 GPs which was analysed using thematic analysis. This design consisted of three distinct phases: quantitative, qualitative, implementation and reflection. Results: Both provider groups acknowledged the complexities of working within mental health care, and supported the development of specific mental health competencies in light of the recognition of the limitations surrounding current mental health care. The unfamiliarity of acupuncture's evidence-base to both provider groups was an identified barrier, yet both groups acknowledged that while practice is informed by the evidence, there are many other factors that also inform clinical practice. Conclusions: This study is the first in New Zealand to seek quantitative data and qualitative views regarding alignment about mental health management approaches and the use of acupuncture. This has the potential of improving healthcare outcomes through better inter professional communication and by contributing to better trans -cultural understandings on healthcare issues. The results of this research, whilst looking at the communication model between acupuncture and primary health care, will have easily generalizable findings for other necessary interprofessional communication strategies. This is the first time that the role and potential of the relatively untapped resource base of acupuncture within the health sector has been investigated within a New Zealand context. Highlights: Mental health presents a significant burden of disease and a large number of patients are now self-selecting CAM. Acupuncture can provide a significant component of integrated care in primary mental health. There are potential risks associated with unmonitored adjunctive use of CAM, communication between treatment providers is encouraged. Provider collaboration has the potential to impact on provider satisfaction and patient wellbeing. Abstract : Mental health presents a significant burden of disease and a large, and increasing, number of patients are self-selecting forms of CAM, including acupuncture, as an adjunct, or standalone treatment for the management of their mental health. General practitioners (GPs) play an important role in integrated care management of primary mental health, and in most cases act as the primary provider and access point for further services. However, the interaction and collaboration between GPs and acupuncturists in relation to shared mental health care has not been investigated. This mixed methods research project explores interprofessional communication between GPs and acupuncturists in New Zealand concerning mental health care. This study is the first in New Zealand to seek quantitative data and qualitative views regarding alignment about mental health management approaches and the use of acupuncture.